9th IEEE International Workshop on Advanced Motion Control, 2006.
DOI: 10.1109/amc.2006.1631688
|View full text |Cite
|
Sign up to set email alerts
|

Cellular neural network based deformation simulation with haptic force feedback

Abstract: Abstract-This paper presents a new methodology for deformable object modelling by drawing an analogy between cellular neural network (CNN) and elastic deformation. The potential energy stored in an elastic body as a result of a deformation caused by an external force is propagated among mass points by the non-linear CNN activity. An improved CNN model is developed for propagating the energy generated by the external force on the object surface in the natural manner of Poisson equation. The proposed methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Neural networks are well-fitted for such tasks, as they are computationally simple, have the ability to map complex and non-linear data relationships and have the ability to learn and then predict in real-time the displayed behavior. This explains the interest of researchers from both the deformable object modeling [5,6] and the grasping and manipulation research fields [7][8][9][10][11] into such techniques.…”
Section: Related Workmentioning
confidence: 98%
See 2 more Smart Citations
“…Neural networks are well-fitted for such tasks, as they are computationally simple, have the ability to map complex and non-linear data relationships and have the ability to learn and then predict in real-time the displayed behavior. This explains the interest of researchers from both the deformable object modeling [5,6] and the grasping and manipulation research fields [7][8][9][10][11] into such techniques.…”
Section: Related Workmentioning
confidence: 98%
“…In the area of deformable object models, object deformation is formulated as a dynamic cellular network that propagates the energy generated by an external force among an object's mass points following Poisson equation in [5]. Greminger et al [6] learn the behavior of an elastic object subject to an applied force, by means of a neural network which has as inputs the coordinates of a point over a non-deformed body (obtained by a computer vision tracking algorithm based on boundary-element method that builds on the equations of the elasticity) and the applied load on the body, and as outputs the coordinates of the same point in the deformed body.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason to use a mesh is that in many cases it is not possible or it is decided not to directly apply the selected phenomena to the anatomical structure being studied. Such decisions are linked to ethical limitations when the subject is alive; the logistics required to apply and record the results of many configu- An exceptional case is noticed in the earliest work considered in this review 30 , where a dynamic cellular NN is used to mimic the deformations experimented by the liver tissue when external forces are applied to it. In this case, the parameters of the network are not trained and their setting is left to the user.…”
Section: Data Collectionmentioning
confidence: 99%
“…Moreover, Zhong et al . showed that a neural network can also be used to predict material deformation based on the theory of conservation of energy . In their paper, the potential energy stored in the elastic body is propagated through mass points by the cellular neural network activity.…”
Section: Introductionmentioning
confidence: 99%